Does universal long-term care insurance boost female labor force participation? Macro-level evidence - Michihito Ando; Masato Furuichi; Yoshihiro Kaneko (IZA Journal of Labor Policy, 2021)
Although a public long-term care (LTC) program is a potentially important factor for the labor supply of female informal caregivers, there are only a handful of individual-level studies on this topic and the macro-level impacts of LTC programs are still largely unknown. Exploiting the introduction of nationwide long-term care insurance (LTCI) in Japan and utilizing a synthetic control method, we examine how LTCI introduction has altered the trends of public expenditures on in-kind benefits for the elderly, public health expenditure, and female labor force participation. The estimation results using the panel data of OECD countries (1980-2013) suggest that LTCI introduction substantially increased the in-kind benefits for the elderly by around one percentage point of GDP 10 years after LTCI introduction, but we do not find a positive effect on the labor force participation for middle-aged women. The fact that we do not observe any positive LTCI effects on middle-aged female labor force participation on a macro level implies that positive LTCI effects on female labor supply observed in some previous microlevel studies may be cancelled out by some other factors or are small enough to be detected under a general-equilibrium setting.
Keywords: H42; H53; H61; I13; J21; J22; 330; long-term care insurance; synthetic control method; aggregate effect; female labor force participation